1994
DOI: 10.1139/f94-299
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Genetic Survey of Sockeye Salmon (Oncorhynchus nerka) in Canada

Abstract: Allozyme variation was examined in sockeye salmon (Oncorhynchus nerka) from 83 distinct spawning sites representing all major sockeye-producing river systems in Canada. Of 33 nonselected loci examined, only 14 were highly polymorphic (q > 0.05) and 10 were less polymorphic (0 < q ≤ 0.05). No two populations were fixed for different alleles at any locus, but allele frequencies ranged from 0.01 to 0.86 at PGM-1* and from 0.07 to 0.89 at ALAT*, the two most variable loci. Mean heterozygosity ranged from 2.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
87
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 20 publications
11
87
2
Order By: Relevance
“…Understanding the patterns of genetic diversity for Cook Inlet sockeye salmon populations has been the focus of a number of studies since the mid-1970s because of the economic importance of these fish (Grant et al 1980;Wilmot and Burger 1985;Burger et al 1997;Seeb et al, in press). Both allozyme and mtDNA data reveal a substantial amount of genetic diversity among populations, and the data support the hypothesis that the nursery lake is the primary unit of reproduction (Seeb et al, in press), a hypothesis used to explain diversity patterns in other portions of the range of the species (Wood et al 1994). Sockeye salmon generally spawn in rivers or smaller creeks associated with nursery lakes and typically exhibit an obligate one-to two-year lacustrine freshwater rearing phase prior to undergoing smoltification and migration to the sea.…”
supporting
confidence: 69%
“…Understanding the patterns of genetic diversity for Cook Inlet sockeye salmon populations has been the focus of a number of studies since the mid-1970s because of the economic importance of these fish (Grant et al 1980;Wilmot and Burger 1985;Burger et al 1997;Seeb et al, in press). Both allozyme and mtDNA data reveal a substantial amount of genetic diversity among populations, and the data support the hypothesis that the nursery lake is the primary unit of reproduction (Seeb et al, in press), a hypothesis used to explain diversity patterns in other portions of the range of the species (Wood et al 1994). Sockeye salmon generally spawn in rivers or smaller creeks associated with nursery lakes and typically exhibit an obligate one-to two-year lacustrine freshwater rearing phase prior to undergoing smoltification and migration to the sea.…”
supporting
confidence: 69%
“…Cultus Lake fish stood apart with near fixation of the ALAT*100 and PGM-1*NULL alleles (see also Wood et al 1994). The two major clusters that contained Lake Washington populations were best distinguished from each other by allelic frequency variation at LDH-A1 and, to a lesser degree, at PGM-1*.…”
Section: Variation Among Populationsmentioning
confidence: 93%
“…This approach has frequently been used to investigate ancestral relationships and to evaluate population differentiation in Pacific salmon (Allendorf and Phelps 1981;Gharrett and Thomason 1987;Utter 1991). For sockeye salmon, biochemical genetic analysis has succeeded in discriminating broad geographical population groups (e.g., Withler 1985;Foote et al 1989;Wood et al 1994), populations from nearby lakes and streams (e.g., Wilmot and Burger 1985;Quinn et al 1987;Grant et al 1980;Varnavskaya et al 1994a), and populations from different spawning locations within lake systems (e.g., Altukhov and Salmenkova 1991;Varnavskaya et al 1994b). For Lake Washington, ancestral origins of the different sockeye salmon populations were inferred through comparisons with the fish currently found in Baker and Cultus lakes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that used numerous allozyme loci as well as those that included samples from a wide geographic area were chosen. The data sets included two studies on Chinook salmon (O. tshawytshca Walbaum- Bartley et al 1992;Waples et al 2004), two on chum salmon (O. keta Walbaum- Phelps et al 1994;Wilmot et al 1994) and two on sockeye salmon (O. nerka Walbaum- Varnavskaya et al 1994;Wood et al 1994) (Table 1). Allozyme alleles frequencies were taken directly from the publications.…”
Section: Methodsmentioning
confidence: 99%
“…5B, C). Analysis of the entire Wood et al (1994) dataset revealed PGM-1 as a high F ST outlier and PGM-2 as a low F ST outlier (Fig. 6A).…”
Section: Sockeye Salmonmentioning
confidence: 99%